Sex-differences in life expectancy at birth: A descriptive analysis of the contributions of age and causes of death to the gap in Norway, 1881–2011 - Valeria Maiolo; Nico Keilman; Finn Gjertsen (Social Sciences and Humanities Open, 2023)
Official mortality statistics provide ample evidence that women live longer than men. In many European countries, the sex difference in life expectancy began to increase near the end of the nineteenth century, peaking between the 1960s and the 1980s, before declining again. In Norway, there was another earlier peak before the sex gap started to converge to that in other European countries.This study investigated changes in sex differences in life expectancy at birth in Norway from 1881 to 2011 as well as the contribution of broad age groups and causes of death to those differences. The total sex gap was broken down by age and cause using decomposition methods. Available mortality statistics were used for every tenth year between 1881 and 2011, excluding the war year of 1941. We regrouped the causes of death into 14 categories to reduce comparability problems across different classification systems.At the end of the 19th century, the gap in life expectancy at birth was largely due to the excessive mortality in males aged 15–29, particularly external causes of death, and in infant mortality in boys (under 1 year) due to perinatal and congenital causes. Since the 1970s, excess mortality in males aged 60 years and over has explained more than half of the sex gap, and the most relevant contributors have been circulatory diseases, neoplasms, and external causes. The recent narrowing of this gap has been related to the increase in pathologies affecting women in old age, such as senility and dementia. Differences in smoking behavior have likely played a role as well: women started smoking a few decades later than men, and they also reduced their smoking later.